2022
DOI: 10.3390/ijms231911726
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Action between Pulsed Radiofrequency and Orthobiologics: Is There a Synergistic Effect?

Abstract: Radiofrequency energy is a common treatment modality for chronic pain. While there are different forms of radiofrequency-based therapeutics, the common concept is the generation of an electromagnetic field in the applied area, that can result in neuromodulation (pulsed radiofrequency—PRF) or ablation. Our specific focus relates to PRF due to the possibility of modulation that is in accordance with the mechanisms of action of orthobiologics. The proposed mechanism of action of PRF pertaining to pain relief reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…The treatments involving local anesthetic blocks of the auriculotemporal nerve and botulinum toxin injections yielded results for our patient that were not entirely satisfactory. Consequently, we decided to apply pulsed radiofrequency as a last resort since this approach successfully treats neuropathic pain conditions, and the short-term and long-term adverse events are very low [ 11 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatments involving local anesthetic blocks of the auriculotemporal nerve and botulinum toxin injections yielded results for our patient that were not entirely satisfactory. Consequently, we decided to apply pulsed radiofrequency as a last resort since this approach successfully treats neuropathic pain conditions, and the short-term and long-term adverse events are very low [ 11 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of refractory cases is challenging, and the literature needs to be more conclusive. Pulsed radiofrequency (PRF) is a common treatment modality for chronic pain [ 11 ]. Pulsed radiofrequency (PRF) is a technique that applies radiofrequency electrical current to a target nerve; the electrical current is of short duration (20 ms) and is followed by a resting phase (480 ms) that repeats for a specific time [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported to decrease levels of interleukin 1. Metalloproteinase -3 and tumor necrosis factor-alpha in the tissues after treatment [ 2 ]. It can also enhance the noradrenergic and serotonergic pain inhibitory pathway and damage nociceptive C and A delta fibers affecting their functioning [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…PRF is an important and effective interventional treatment for chronic neuropathic pain disorders. It generates an electromagnetic field in the pain region that acts on several biological pathways, including ion channels, neurotransmitters, postsynaptic receptors and immune activities,16 thus eliciting a neuromodulation effect 17. Recent studies have reported that ultrasound-guided PRF might also be a promising treatment for chronic MPS 18–21.…”
Section: Introductionmentioning
confidence: 99%